The Effect of Eight Weeks of Strength Training on Selected Biomechanical Properties of Femur in Old Male Rats - Sima Mohammad Amoli; Heydar Sadeghi (Islamic Azad University, Hamedan Branch, 2017)
objective: The purpose of this study was to determine the effect of eight weeks of strength training on some chosen biomechanical properties of femur of old male rats.  Methods: In this experimental research sixteen old male Wistar rats around Twenty months old were assigned to sedentary control group (n=8) and strength training group (n=8). Strength training group climbed from a ladder for 8 weeks, 4 times per week. Forty eight hours after last session of exercise training, animals were anesthetized and femur bones were removed. Three – point bending test was used to determine bone biomechanical properties. The data was analyzed by independent samples t test (p≥0.05).  Results: The results showed that such training would not significantly affect on bone stiffness, fracture energy and maximal load (p>0.05). Conclusion: A possible explanation for this lack of effect can be intensity, type and time of training or the age at which such training states.